A STUDY OF TEACHING STRATEGIES IN IMPROVING ENGLISH READING COMPREHENSION SKILL: A CASE STUDY OF SHARIA BUSINESS MANAGEMENT STUDENTS OF IAIN KEDIRI - Hamida, Ulfi Dina; Farikha, Ninik (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
Reading is one of essential things in academic world. Most of refferences such as books, journal articles, online information, terms in academic study use English as the languange. Understanding an English text related to their major is a must to enrich literacy of the students. This study aims to investigate teaching strategies in improving English reading comprehension skill, It is carried out based on case study of sharia business management students of IAIN Kediri in English text study class. This study used qualitative descriptive method. The data is taken from observation, interview and documentation. This study tries to describe the strategies used by lecturers to overcome problems that arise related to reading comprehension skills in English text study class on Islamic business management c in FEBI IAIN Kediri. In the teaching process there are three stages implemented which aim to improve reading comprehension skills. The first stage is reading orientation and technique, namely the introduction of reading orientation, enriching vocabulary and learning reading techniques. then the second is compiling a summary that aims to measure and sharpen students' understanding of the reading and the last is evaluation. This strategy has proven to be effective in overcoming students' reading problems. this is evidenced by the increase in reading comprehension skills. Besides that, it is also proven by test results that pass the minimum standard score.